Forced transnationalism and temporary labour migration: implications for understanding migrant rights. Issue 5 (3rd September 2018) - Piper, Nicola; Withers, Matt
ABSTRACT: International labour migration is inherently a transnational phenomenon that reflects the changing composition of labour markets and labour systems and has resulted in the rising presence of non-citizens in places of work. While the transnationalism literature has made important contributions by shifting empirical attention beyond national boundaries, so too has it overstated migrant agency while downplaying the relevance of state power. This paper draws on the concept of protracted precarity, as it applies to temporary labour migration within key migratory corridors in Asia, to develop an alternative paradigm of forced transnationalism that better accounts for transnationalism in the absence of meaningful agency. Three prominent features of cross-border labour migration are examined: temporary employer-tied contracts, commercialised recruitment, and feminised migration. This leads on to a discussion of the specifically transnational dimensions of the curtailed economic and political rights that produce migrant precarity and precarious livelihoods.